0416 Inability to Discontinue Chronic Hypnotic Use. (27th April 2018) - Koshorek, G; Withrow, D; Roth, T; Roehrs, T
Abstract: Introduction: Inability to discontinue chronic hypnotic use by people with insomnia remains a clinical concern. However, that inability has never been directly tested in a controlled prospective study using self-administration choice procedures. This is a preliminary report of results from an on-going "blinded" clinical trial in which people with insomnia are instructed to stop taking their study medication after 6 months of nightly use. Methods: DSM-V diagnosed people with insomnia (n=19, 17 females), aged 26–58 yrs, with a polysomnographic sleep efficiency of ≤85%, no other sleep disorder, unstable medical or psychiatric diseases or drug dependency completed the clinical trial. On a Multiple Sleep Latency Test (MSLT) 8 had average latencies >12 min and 11 had latencies of 11- 5 min. Participants were randomized to zolpidem XR (12.5 mg), eszopiclone (3 mg) or placebo nightly for 6 months (blinded groups A: n=7, B: n=5, C: n=7). After 6 months, over a 2-week choice period, they were given the instruction to discontinue their nightly hypnotic use with an opportunity, if necessary, to self-administer either 1, 2, or 3 capsules of their assigned medication (zolpidem XR 6.25 mg, 6.25 mg, placebo; eszopiclone 2 mg, 1 mg, placebo as capsules 1, 2 and 3 respectively; or 3 placebos). Results: The total number of capsules taken declined from week 1 to 2 (p< .01). Over the 2 weeks 15 participants took < 5 total capsules (8 took 0, 2-1, 2-2, 1–3, 2–4 caps). Four participants took >5:1 each took 42, 19, 13, and 10. These 4 were younger (p<.05), but did not differ in screening sleep efficiency or MSLT. Conclusion: The majority (79%) of the participants were able to discontinue 6-month nightly hypnotic use (i.e. took < 5 total capsules) and among those taking capsules the rate declined from week 1 to 2. Age may help identify the few with difficulty discontinuing. Support (If Any): NIDA, grant#: R01DA038177 awarded to Dr. Roehrs.